1996
DOI: 10.1149/1.1837114
|View full text |Cite
|
Sign up to set email alerts
|

An Electrical Model for the Cathodically Charged Aluminum Electrode

Abstract: A mathematical model was formulated for the surface film on aluminum which considered the film to consist of an inner barrier high-field conducting layer and an outer, porous, ohmically conducting layer. It included all relevant capacitive and faradaic processes, and incorporated the nonlinearity of conduction and reaction rate expressions. The model was used to investigate structural changes produced by cathodic polarization in acid solutions, which has been found to promote anodic pitting strongly in ac etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The role of the cathodic half-cycle in the ac etch process has been explained in terms of (i) the formation of a precipitated aluminum oxyhydrate ‘etch film’ due to the increase in the local pH during the cathodic half-cycle [76, 91]; (ii) the hydration of the surface oxide film [92–94]; or (iii) the mechanical deterioration of the surface oxide film due to hydrogen gas generation [9597]. In ac electrograining, Dyer and Alwitt [91] proposed a pit-on-pit propagation mode.…”
Section: Ac Anodizationmentioning
confidence: 99%
“…The role of the cathodic half-cycle in the ac etch process has been explained in terms of (i) the formation of a precipitated aluminum oxyhydrate ‘etch film’ due to the increase in the local pH during the cathodic half-cycle [76, 91]; (ii) the hydration of the surface oxide film [92–94]; or (iii) the mechanical deterioration of the surface oxide film due to hydrogen gas generation [9597]. In ac electrograining, Dyer and Alwitt [91] proposed a pit-on-pit propagation mode.…”
Section: Ac Anodizationmentioning
confidence: 99%
“…The film after cathodic polarization is likely porous based on the deuterium exchange experiment by Lin 48 , and film conductance measurements using the QCM 49 . Wang and Hebert 50 investigated the structure change of oxide film on aluminum due to cathodic charging using transient electrochemical measurements. They found a decrease of the inner pore-free layer thickness and an increase of porosity of the outer porous layer.…”
Section: Evidence For Defects In Oxidesmentioning
confidence: 99%
“…From Quartz Crystal Microbalance (QCM) experiments [9], they found further indications that no significant oxide dissolution occurs during the cathodic polarization period. Wang and Hebert [10] found that cathodic polarization leads to a decrease in barrier layer thickness and an increase in porosity. Their work is described in greater detail below.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
“…After studying the initial stages of cathodic breakdown of thin anodic aluminum oxide films, Hassel and Lohrengel [10] proposed a mechanism for cathodic breakdown of the film.…”
Section: Afm Probesmentioning
confidence: 99%
See 1 more Smart Citation